EFFECT OF SOCIO-ECONOMIC CHARACTERISTICS OF FARMERS ON DEFORESTATION ADAPTATION STRATEGIES IN MUBI-SOUTH LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NIGERIA - ABDULLAHI, Aliyu; USMAN, Ibrahim S.; A. GIREI, Abdulhameed (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The study examines the effect of socio-economic characteristics of farmers on deforestation adaptation strategies in Mubi South Local Government Area of Adamawa State, Nigeria. Primary data were collected from 120 farmers using purposive and random sampling techniques. The data collected were analysed using descriptive statistics, Likert-Scale and Multiple regression analysis. Result of the analysis revealed that most (86.7%) of the respondents were within the ages of 20-50 years, educated (97.5%), male (86.7%) and married (70.0%) with household sizes of 6-10 persons (58.3%). Most of the respondents (91.7%) had between 11 and 21 years of farming experience. Similarly, the use of fuel efficient wood stove, use of corn straw for cooking, domestication of medicinal plants and conservation agriculture were ranked foremost among the deforestation adaptation strategies being used by the respondents in the area. In determining the relationship between socio-economic characteristics of the respondents and deforestation adaptation strategies, the result of the multiple regression used shows that, age, education level, farming experience and extension contacts positively influences deforestation adaptation strategies. Among the constraints faced by the respondents include: lack of capital (23%), resistance to change (22.3%), and lack of awareness (22.0%). It is recommended that Government and other NGOs should provide adequate funding to engage in various deforestation adaptation strategies by sustaining in its environmental initiative programmes under the current agricultural transformation agenda and efforts should be intensified in educating farmers through concerted efforts of extension agents and agricultural radio programmes with the view of ensuring proper guide and educating farmers on effective deforestation strategies to be adopted.